Teacher trainees preference of the end-product over the writing process in ESL writing classrooms - Palpanadan, Dr. Sarala @ Thulasi; Sathappan, Ramesh; Md Yunan, Noreida (IPGK Temenggong Ibrahim, 2016)
This study investigates the preference of teacher trainees in adopting product approach (PDA) and process approach (PCA) as writing instructions in Malaysian ESL classrooms. The PDA focuses on the end product while PCA targets the development of the writing process. The PDA which is popular in the contemporary ESL classrooms seems to be beneficial in several ways. Teachers are able to cover syllabus and topics on time and reach out to students by assessing students' writing. Meanwhile, the PCA, which is less popular currently, helps students to get involved in the writing process by producing several drafts and become less fearful to start writing. Hence, this stuch, analyzes the features of both the approaches in detail. This paper hopes to be an illuminating factor in terms of writing instructions to help the students to learn necessary writing skills and benefit the teacher trainees to teach writing more convincingly in future.